Pelatihan English For Spesific Purposes (ESP) untuk Pemasaran Digital Berbasis Budaya bagi Karyawan PT. Bali Sundaram Travel: Penelitian - I Nyoman Kardana; Dewa Ayu Kadek Claria; Ni Made Suwendri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The rapid growth of businesses in the tourism sector in Bali has created fierce competition. This unavoidable business competition demands the development of appropriate business strategies to avoid the decreasing interest of buyers. PT. Bali Sundaram Travel, as one of the companies engaged in travel management services, also faces these challenges. The first issue relates to competition in promoting app-based products by Online Travel Agents (OTA). The second issue concerns the efforts to increase sales by developing culture-based promotional content in English. To address those two challenges, specific training was conducted to improve employees’ English skills in the service sector, especially for handling complaints and upselling.